Toxicological Evaluations of Rare Earths and Their Health Impacts to Workers: A Literature Review - Rim, Kyung Taek; Koo, Kwon Ho; Park, Jung Sun (Safety and health at work, 2013)
In concert with the development of new materials in the last decade, the need for toxicological studies of these materials has been increasing. These new materials include a group of rare earths (RE). The use of RE nanotechnology is being considered in some green applications, to increase their efficiency by using nano-sized RE compounds, and therefore hazard evaluation and risk assessment are highly recommended. This review was conducted through an extensive contemplation of the literatures in toxicology with in vitro and in vivo studies. Major aspects reviewed were the toxicological evaluations of these elements and metallic compounds at the molecular and cellular level, animal and human epidemiological studies and environmental and occupational health impacts on workers. We also discuss the future prospect of industries with appliances using RE together with the significance of preventive efforts for workers’ health. To establish a safe and healthy working environment for RE industries, the use of biomarkers is increasing to provide sustainable measure, due to demand for information about the health risks from unfavorable exposures. Given the recent toxicological results on the exposure of cells, animals and workers to RE compounds, it is important to review the toxicological studies to improve the current understanding of the RE compounds in the field of occupational health. This will help to establish a sustainable, safe and healthy working environment for RE industries.